Fatty Acids Extraction from Oil Palm Mesocarp Fiber Through Synergistic Effect of Supercritical Carbon Dioxide and Ethanol as Co-Solvent - YIN YAN, SUM (IRC, 2017)
Oil palm biomass has been utilizing for extracting fatty acids and other value added products by applying the supercritical fluid extraction (SFE) technique. The research employed the combination of supercritical carbon dioxide and ethanol as co-solvent to extract value-added products from palm mesocarp fiber (PMF). The effect of extraction temperature ranging from 40- 80℃, pressure of 20- 40 MPa and flow ratio of ethanol (4- 8% of the CO2 flowrate) were studied to enhance the extraction yield. The statistical result of the experiment showed that the extraction pressure, co-solvent flow ratio, and interaction between temperature and pressure had significant effect on extracted oil yield. The optimum conditions for Sc-CO2 extraction with addition of ethanol was at 76.82 ℃, 39.6 MPa and 0.29 ml/min. The experimental yield was 7.8 wt% which was close to the predicted yield by the model was 8.2 wt%. ANOVA analysis showed that the model has a satisfactory level of R2 (0.9374) and adjusted R2 (0.8810) which had confirmed the validity of the model. The bio-yield extracted by Sc-CO2 extraction was higher than that of Soxhlet extraction (4 wt%). Besides that, the fatty acid constituents of the extracted oil yield by Sc-CO2 extraction and Soxhlet extraction were characterized by gas chromatography–mass spectrometry (GC-MS) and Fourier transform infrared spectrometer (FTIR). The results indicated that the fatty acid composition in the extracted oil from both methods were almost similar. The major fatty acids detected were oleic acid (42.08 %), palmitic acid (36.26 %), lauric acid (5.66 %), stearic acid (4.10 %) and myristic acid (2.56 %).